2012
DOI: 10.1128/jb.06328-11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Periodontal Pathogens on the Metatranscriptome of a Healthy Multispecies Biofilm Model

Abstract: Oral bacterial biofilms are highly complex microbial communities with up to 700 different bacterial taxa. We report here the use of metatranscriptomic analysis to study patterns of community gene expression in a multispecies biofilm model composed of species found in healthy oral biofilms (Actinomyces naeslundii, Lactobacillus casei, Streptococcus mitis, Veillonella parvula, and Fusobacterium nucleatum) and the same biofilm plus the periodontopathogens Porphyromonas gingivalis and Aggregatibacter actinomycetem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
79
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 85 publications
7
79
1
Order By: Relevance
“…Notably, functions related to bacterial motility, energy metabolism, lipopolysaccharide (LPS) biosynthesis, flagellar assembly, methane metabolism, bacterial chemotaxis, and peptidases were abundant in chronic periodontitis cases. These results are consistent with recent metagenomic data (34,53). Going forward, elucidating the role of key bacteria encoding these functions and understanding the basis of individual variations in microbiomes and metagenomes will be essential in future studies.…”
Section: Discussionsupporting
confidence: 78%
“…Notably, functions related to bacterial motility, energy metabolism, lipopolysaccharide (LPS) biosynthesis, flagellar assembly, methane metabolism, bacterial chemotaxis, and peptidases were abundant in chronic periodontitis cases. These results are consistent with recent metagenomic data (34,53). Going forward, elucidating the role of key bacteria encoding these functions and understanding the basis of individual variations in microbiomes and metagenomes will be essential in future studies.…”
Section: Discussionsupporting
confidence: 78%
“…The metatranscriptome refers to the gene expression of the whole microbial community [12]. Previous studies have shown differences in microbial gene expression based on sample site within the oral cavity [13] between health and periodontitis [14] and dental caries [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…We had previously observed the upregulation of putative transposases in an S. mitis biofilm in a multispecies biofilm model where two periodontal pathogens (P. gingivalis and A. actinomycetemcomitans) were added simultaneously (8). We first verified the upregulation of these putative transposases when only P. gingivalis was added.…”
Section: Resultsmentioning
confidence: 83%
“…As mentioned above, in a previous metatranscriptomic analysis we observed a high upregulation of a large number of putative trans-posases in S. mitis expression profiles when P. gingivalis and Aggregatibacter actinomycetemcomitans were added to an established healthy biofilm (8). Upregulation of putative transposases has been observed by Mitchell et al in the periodontal pathogen T. denticola when growing as a biofilm but not in planktonic growth, concluding that there is a higher potential for genetic mobility in T. denticola biofilms (16).…”
mentioning
confidence: 90%
See 1 more Smart Citation